A review of the species of the tribe Chorosomatini of China (Hemiptera: Heteroptera: Rhopalidae) - Rédei, Dávid (Zootaxa, 2018)
Species of the tribe Chorosomatini (Hemiptera: Heteroptera: Rhopalidae: Rhopalinae) occurring in China are reviewed. Type materials of three species described from China, so far of uncertain identities, are re-examined and documented, and taxonomic changes are accordingly proposed. The following synonymies, suspected but not explicitly proposed by previous authors, are confirmed and explicitly proposed: Agraphopus lethierryi Stål, 1872 = A. yunnanus Hsiao, 1965; Leptoceraea viridis Jakovlev, 1873 = L. granulosa Hsiao, 1965; Chorosoma macilentum Stål, 1858 = Ch. brevicolle Hsiao, 1964. Faunistic records of other species of the tribe are provided, and several misidentifications in the previous literature are corrected; Ch. gracile Josifov, 1968, and Ch. schillingii (Schilling, 1829) are recorded for the first time from China. A checklist of the species and subspecies of Chorosomatini occurring in China, with a review of their distribution, and a key for their identification, are provided.